Adult-onset atopic dermatitis - Amrinder Jit Kanwar (Wolters Kluwer Medknow Publications, 2016)
Adult-onset atopic dermatitis is still an under recognized condition as there are only few studies regarding this entity. As compared to childhood onset atopic dermatitis, clinical features of adult onset atopic dermatitis are still not categorized. Adult atopic dermatitis can present for the first time in adult age with atypical morphology or may progress from childhood onset. This article reviews the characteristic clinical features of adult atopic dermatitis, associated risk factors and management.